Do norms make preferences social? Supporting evidence from the field - Christoph Rößler; Hannes Rusch; Tim Friehe (ZBW - Leibniz-Informationszentrum Wirtschaft, 2019)
We examine whether compliance with the law is associated with prosocial behavior. We test whether people who comply with parking rules are more likely to reply to a survey than people who did not comply with parking rules. We find that parking rule followers have significantly higher response rates than parking rule violators. The responses of the surveys suggest, that the evaluation of the parking rule violation is associated with the decision to park correctly. Economic considerations like the expected sanction level or the detection probability do not seem to influence the decision to park correctly.
Keywords: 330; Prosocial behavior; Law; Norms